A QUANTITATIVE APPROACH TO SUBSIDIZE THE PRECAUTIONARY MANAGEMENT of THE SMALL-SCALE FISHERIES IN ITAIPU RESERVOIR, BRAZIL - Franco de Camargo, Serguei Aily; Okada, Edson Kiyoshi; Petrere, Miguel [UNESP] (Inst Pesca, 2008)
Professional inland fisheries are an important economic activity in the region of Itaipu reservoir. The dam was closed in 1982, and in 1998, 619 professional fishermen landed 1192t of fish, composing 10 commercial species. In the 1990s there were 509 fishermen month(-1) on average working in the reservoir. This number falls to approximately 365 fishermen month(-1) between 2000 and 2002 as a consequence of the fishing ban. The reservoir consists of 12 fishing areas, distributed in 3 zones: fluvial (influenced by Parana River), transition (influenced by the tributaries) and lacustrine (near the dam). There were differences in fishermen densities in these zones: 42% work in the lacustrine, 41% in the fluvial and 17% in the transition. The main fishing gears employed is nets and hooks. The Itaipu royalties' payment to the municipalities in the region may possibly incentive the reduction of the level of professional fisheries. Between 1991 and 2001, it has been observed that there is a strong negative relation between the amount of royalties paid and the level of fishing effort. In this context, it was proposed a preliminary bio-mathematical model to subsidize the formulation of guidelines, based on the statements of precautionary management, as the predominant orientation in the literature. It was elaborated a model via the software Vensim PLE to describe and predicting small-scale fisheries consequences upon the reservoir fish stock, and it was tested the relation between the decrease of fishing effort and Itaipu royalties' payment to the municipalities via a regression model.